Subjects With Early-Onset Type 2 Diabetes Show Defective Activation of the Skeletal Muscle PGC-1α/Mitofusin-2 Regulatory Pathway in Response to Physical Activity - Hernández-Alvarez, María Isabel; Thabit, Hood; Burns, Nicole; Shah, Syed; Brema, Imad; Hatunic, Mensud; Finucane, Francis; Liesa, Marc; Chiellini, Chiara; Naon, Deborah; Zorzano, Antonio; Nolan, John J (Diabetes care, 2010)
OBJECTIVE: Type 2 diabetes is associated with insulin resistance and skeletal muscle mitochondrial dysfunction. We have found that subjects with early-onset type 2 diabetes show incapacity to increase VO₂max in response to chronic exercise. This suggests a defect in muscle mitochondrial response to exercise. Here, we have explored the nature of the mechanisms involved. RESEARCH DESIGN AND METHODS: Muscle biopsies were collected from young type 2 diabetic subjects and obese control subjects before and after acute or chronic exercise protocols, and the expression of genes and/or proteins relevant to mitochondrial function was measured. In particular, the regulatory pathway peroxisome proliferator-activated receptor γ coactivator (PGC)-1α/mitofusin-2 (Mfn2) was analyzed. RESULTS: At baseline, subjects with diabetes showed reduced expression (by 26%) of the mitochondrial fusion protein Mfn2 and a 39% reduction of the α-subunit of ATP synthase. Porin expression was unchanged, consistent with normal mitochondrial mass. Chronic exercise led to a 2.8-fold increase in Mfn2, as well as increases in porin, and the α-subunit of ATP synthase in muscle from control subjects. However, Mfn2 was unchanged after chronic exercise in individuals with diabetes, whereas porin and α-subunit of ATP synthase were increased. Acute exercise caused a fourfold increase in PGC-1α expression in muscle from control subjects but not in subjects with diabetes. CONCLUSIONS: Our results demonstrate alterations in the regulatory pathway that controls PGC-1α expression and induction of Mfn2 in muscle from patients with early-onset type 2 diabetes. Patients with early-onset type 2 diabetes display abnormalities in the exercise-dependent pathway that regulates the expression of PGC-1α and Mfn2.